Nilai-Nilai Pendidikan Dalam Al-Qur’an: (Studi Analisis Surat Al-Muddaṡṡir Ayat 1-7) - Juhri Jaelani; Tatang Hidayat; Istianah Istianah (ZAD Al-Mufassirin, 2022)
Learning in a thriving life setting has a dialectic of change that never stops, giving rise to many speculations regarding the characteristics of ideal educators and learners. This study aims to describe the values of education based on the analytical study of surah Al-Muddaṡṡir verses 1-7. This research uses a qualitative approach with a literature method. The data collection technique in this study uses a descriptive analysis method by reading, understanding and analyzing Surat Al-Muddaṡṡir starting from letters, vocabulary (muphrodat) to the verses. The results showed that the Qur'an contains many educational messages in human life. Among other things, it explains the characteristics of educators and students who are ideal in the teaching and learning process. Educators and students must have sincere, clean and sincere intentions when they want to start learning. Educators and participants must also be clean from all kinds of dirt and uncleanness. As well as from all liver diseases, namely envy, hasud, arrogant spite and so on.